2017
DOI: 10.1111/cts.12525
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Analysis of the Model‐Based Pharmacokinetics of Five Anti‐HIV Drugs: How Does This Influence the Effect of Aging?

Abstract: Analysis of aging and pharmacogenetics (PGx) on antiretroviral pharmacokinetics (PKs) could inform precision dosing for older human HIV‐infected patients. Seventy‐four participants receiving either atazanavir/ritonavir (ATV/RTV) or efavirenz (EFV) with tenofovir/emtricitabine (TFV/FTC) provided PK and PGx information. Aging‐PGx‐PK association and interaction analyses were conducted using one‐way analysis of variance (ANOVA), multiple linear regression, and Random Forest ensemble methods. Our analyses associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 14 ABCB1 rs3213619 was associated with increased tenofovir bioavailability in a predominantly African-American patient population ( n = 45) and thought to be a result of decreased P-glycoprotein function. 21 A genome-wide and candidate gene association analyses with tenofovir pharmacokinetics showed that SLC17A1 rs12662869 was associated with an increase in tenofovir clearance ( p = 7.1 × 10 −9 ) but failed to show significant associations in candidate genes (including ABCC4, ABCC10, ABCB1, ABCC2, SLC22A11, AK2 and AK3 ) after correction for multiple comparisons. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 14 ABCB1 rs3213619 was associated with increased tenofovir bioavailability in a predominantly African-American patient population ( n = 45) and thought to be a result of decreased P-glycoprotein function. 21 A genome-wide and candidate gene association analyses with tenofovir pharmacokinetics showed that SLC17A1 rs12662869 was associated with an increase in tenofovir clearance ( p = 7.1 × 10 −9 ) but failed to show significant associations in candidate genes (including ABCC4, ABCC10, ABCB1, ABCC2, SLC22A11, AK2 and AK3 ) after correction for multiple comparisons. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Increased CYP2B6 (or other hepatic enzyme) activity would explain lower systemic efavirenz exposure with increasing estradiol concentrations. Similarly, efavirenz is a substrate for efflux drug transporter MRP4, 10 , 11 which like CYP2B6 may also be induced by estradiol. Increased expression of efflux drug transporter in the gut epithelium may point to decreased efavirenz absorption and is consistent with our findings of lower efavirenz concentrations with increased estradiol.…”
Section: Discussionmentioning
confidence: 99%